Kinetics of Stability and Pigment Effects from Monascus sp. YRU01 Used as a Food Coloring in Chicken Sausages - Louhasakul, Yasmi; Kode, Asiyan; Samae, Sofianee; Tayeh, Nutchanet (YRU Journal of Science and Technology, 2024)
Color stability and the factors affecting the stability at various processing conditions are crucial for color application in food. Therefore, this research aims to evaluate the effect of pH and temperature on Monascus sp. YRU01 pigment stability in order to apply the pigment as a food coloring in chicken sausages. The pH covering acidified and low-acid foods (pH 3.0 – 8.0) and the temperature covering food processing temperature (-20, 0, 63, 100, and 121 °C) were studied. The pigment was highly stable at pH 7.0 - 8.0 with a half-life of 16 - 29 days and greatly stable at 0 °C with a half-life of 4 months. In addition, it was favorably stable at high temperature of 63 - 100 °C. These demonstrated the possibility of the pigment application as a food coloring in chicken sausages. It was found that the addition of pigment significantly increased the redness (a*) of chicken sausage (p≤0.05) and also significantly increased color and odor acceptance scores (p≤0.05). The results indicated the potential of Monascus sp. YRU01 pigment could be used as a food coloring in food products.